Ethical Businesses: A Win-Win for All (Trinity Journal of Management, IT & Media (TJMITM), 2021)
The primary objective of establishing a business whether small or big, national or global, trading or manufacturing or providing goods or services, is to make profits. The yardstick of measuring the success of business has since long been the earning of profits and more the profits, the happier is the owners. At personal level or individual level, making profits is the biggest incentive to put in hard work. And at the corporate level, maximising the earnings of shareholders is the litmus test for the survival and growth of business enterprises. The simplest question relates to the modus operandi through which business makes profits. Basically, the task of converting raw materials into finished products by creating utility in these and transporting them to places where these products are needed is the way a basic business enterprise is defined. So, in these processes, suppliers, employees, customers and governments are directly involved as they tend to benefit or lose monetarily and are also impacted non-monetarily from business operations. And at a larger level, the society and humanity at large can be affected by the way business is operated because the resources provided by nature are scarce and the powerful corporate sector tries to monetise this environmental capital, thus endangering the survival of the human species. The corporate sector, in its short sightedness of making quick and large profits, can bypass the ethical and moral standards, putting the humanity to many types of risks and dangers, increased threat to environment and climate, violation of human rights, rapidly rising inequalities along with the enhanced awareness of consumers, investors and communities about business ethics has brought the issue to the forefront during the course of the fourth industrial revolution. At various for at the international level, the businesses are converging on the idea of doing business more purposefully than solely keeping shareholders profits in view.
Keywords: Business; survival; ethics; danger; humanity; sustainable